Glaciations in Patagonia and Tierra del Fuego during the Ensenadan Stage/Age (Early Pleistocene-earliest Middle Pleistocene) - Rabassa, Jorge Oscar; Coronato, Andrea Maria Josefa (Quaternary International)
While the Ensenadan Stage/Age (ca. 2.1 to 0.5 Ma) was characterized by certain mammal associations in the Pampean plains, the Andean ranges of Patagonia and Tierra del Fuego, their piedmont areas and, in some cases, the adjacent lowlands were undergoing a well-defined alternating sequence of glacial and interglacial stages driven by the regional climate of Southernmost South America and Antarctica. This paper reviews the available geographical, geological and chronological evidence of glaciation during the Ensenadan stage/age, with perhaps more than 15 distinct glacial events, including the Great Patagonian Glaciation (GPG) and other cold episodes that took place before and after it. Finally, a tentative correlation of Patagonian glacial episodes and the Pampean biostratigraphic stages, based on radiometric dating and paleomagnetic studies, is herein presented. Fil: Rabassa, Jorge Oscar. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Coronato, Andrea Maria Josefa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de la Patagonia Austral; Argentina